Performance of PRECISE-DAPT and Age–Bleeding–Organ Dysfunction Score for Predicting Bleeding Complication During Dual Antiplatelet Therapy in Chinese Elderly Patients - Dong, Liang; Lu, Cao; Wensen, Chen; Fuzhong, Chen; Khalid, Muhammad; Xiaoyu, Dong; Guangjuan, Li; Yanxia, Qian; Yufeng, Zhang; Xinjian, Liu; Leilei, Chen; Junhong, Wang (Frontiers in Cardiovascular Medicine, 2022)
Recently, the Age–Bleeding–Organ Dysfunction (ABO) algorithm was recommended by Asian Pacific Society of Cardiology Consensus as a binary approach to evaluate bleeding risk. This analysis made comparison of the predictive performances between the PRECISE-DAPT and ABO bleeding score in identifying the risk of 12-months major bleeding in Chinese elderly patients over 65 years old patients who underwent percutaneous coronary intervention during dual-antiplatelet therapy period.